2021
DOI: 10.3389/fphys.2021.774095
|View full text |Cite
|
Sign up to set email alerts
|

Lactic Acid Transport Mediated by Aquaporin-9: Implications on the Pathophysiology of Preeclampsia

Abstract: Aquaporin-9 (AQP9) expression is significantly increased in preeclamptic placentas. Since feto-maternal water transfer is not altered in preeclampsia, the main role of AQP9 in human placenta is unclear. Given that AQP9 is also a metabolite channel, we aimed to evaluate the participation of AQP9 in lactate transfer across the human placenta. Explants from normal term placentas were cultured in low glucose medium with or without L-lactic acid and in the presence and absence of AQP9 blockers (0.3 mM HgCl2 or 0.5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…These two AQPs are identified as aquaglyceroporins that mediate H 2 O and glycerol trafficking [81]. Also, a recent study reveals that AQP9 facilitates monocarboxylates passage into the cytosol and mitochondria [82]. Dysregulation of AQP3 and AQP9 impairs osmoregulation, energy production, and removal of ROS [83,84], which would likely alter mammary function.…”
Section: Spaceflight and Ion-channelsmentioning
confidence: 99%
“…These two AQPs are identified as aquaglyceroporins that mediate H 2 O and glycerol trafficking [81]. Also, a recent study reveals that AQP9 facilitates monocarboxylates passage into the cytosol and mitochondria [82]. Dysregulation of AQP3 and AQP9 impairs osmoregulation, energy production, and removal of ROS [83,84], which would likely alter mammary function.…”
Section: Spaceflight and Ion-channelsmentioning
confidence: 99%
“…All of the above studies imply that lactate may play a crucial role in the microenvironment of PE patients. Although the work of Yollyseth Medina et al confirmed that CTB hypoxia in PE patients activates anaerobic glycolysis leading to a functional defect in lactate transport proteins, which in turn leads to excessive lactate accumulation and promotes excessive protein lactation (19)(20)(21). However, the effect of hypoxia-induced protein hyperlactivation on PE has never been explored.…”
Section: Introductionmentioning
confidence: 99%